Long-term results of treatment for patients with locally advanced external ear skin cancer - A. M. Mudunov; E. G. Khazarova; M. V. Bolotin (Опухоли головы и шеи)
The study objective is to assess long-term results of treatment for patients with locally advanced external ear skin cancer.Materials and methods. This research work based on a retrospective and prospective analysis case history for patients with locally advanced external ear skin cancer. These are 45 patients, who received treatment in surgical department of head and neck tumors in Blokhin National Medical Research Center of Oncology between 1994 and 2020. Patient observation time averaged 30.0 ± 32.3 months (from 0.7 to 117.4 months, median 12.0 months). We divided patients into 3 groups depending on treatment methods. Group 1 consisted of patients who received combined or complex treatment (33.3 %, n = 15). Treatment for first group patients involved subtotal, lateral temporal bone resection or incomplete lateral resection and postoperative radiation therapy on the area of primary tumor and regional metastasis zone (total focal dose from 60 Gy). In the case of complex treatment, radiation therapy had carried out against background cisplatin introduction. The second group consisted of patients who received only surgical treatment (40.0 %, n = 18). Temporal bone resections were not performed for patients of the third group (26.7 %, n = 12). Treatment for patients of the third group involved one of the treatment methods: cryodestruction, laser destruction, photodynamic therapy, radiotherapy or chemoradiation treatment.Results. Five-year survival without signs of progression in a group of patients with locally advanced of the ear skin cancer, who received combined or complex treatment was 73.8 ± 13.1. Median progression-free survival not achieved. In the surgical treatment group 5 year progression-free survival was 40.4 ± 13.0, median was 34.1 months. In a group of patients who did not undergo temporal bone resection (3rd group) median progression-free survival was 4.5 months. Group differences are statistically significant (p <0.05). The most significant adverse prognosis factors that reduce overall survival for patients with locally advanced external ear skin cancer are positive histological margin (p = 0.0001, hazard ratio (HR) = 10.611, 95 % confidence interval (CI) 3.058-36.820), signs of destruction branch of the lower jaw/ zygomatic bone (p = 0.027, HR = 4.65, 95 % CI 1.193-18.116). Facial paralysis is the most unfavorable prognosis factor, reducing tumor-specific survival in patients with locally advanced outer ear skin cancer (p = 0.0001, HR = 19.146, 95 % CI 4.056-90.388).Conclusion. Combined/complex treatment of patients with locally advanced ear skin cancer (surgery with postoperative radiotherapy/chemoradiotherapy) provides better long-term results compared to other treatment options.